Editor’s introduction - Keane, Michael (Bloomsbury Academic, 2011)
It is a very rare event when a book by a senior Chinese policy adviser gets published in English. More often the accepted format is biography or auto-biography, generally published once the person has retired. This book was first published by Xinhua Press in Chinese in a longer version in 2009. Initially it was directed at the Chinese reader, more specifically the Chinese cultural academic, and for this reason some of the material is not repeated in this abridged version. Nevertheless, it is important to point out that the author represents four speaking positions, and the messages that emerge from this work need to be contextualized accordingly.